DEVELOPMENT OF THE ADAPTIVE VARIATIONAL QUANTUM EIGENSOLVER (VQE) METHOD AS A QUANTUM SIMULATION ALGORITHM - Ikhtiarudin, Azhar
Quantum simulation aims to model and predict the properties of quantum systems, which are useful in various fields such as material design, pharmaceuticals, and chemical reaction analysis using computation. The main challenge in quantum simulation methods is the inability of current computers to efficiently handle the complexity of quantum systems, as this complexity increases exponentially with the size of the system considered. One proposed solution to address this issue is using quantum computers, which operate based on the laws of quantum mechanics. The development of quantum computers is currently in the NISQ (Noisy Intermediate- Scale Quantum) era, which means they have limited qubits and are susceptible to derau interference. Despite these limitations, researchers are striving to utilize them by developing hybrid algorithms that run on both classical and quantum computers. One such hybrid algorithm used in quantum simulation is the Variational Quantum Eigensolver (VQE). The VQE algorithm still requires further development to be more accurate and efficient. One development effort is the ADAPT-VQE algorithm, which utilizes adaptive quantum circuits constructed specifically for each case under consideration. In this study, implementation programs for the VQE and ADAPT-VQE algorithms will be developed and tested on calculating the ground state energy of H2, LiH, and N2H4 molecules. The research results show that in general, ADAPT-VQE is more efficient in terms of the number of quantum gates and circuit depth for each tested molecular case. ADAPT-VQE also could achieves higher accuracy than VQE when compared to precise reference values in classical computation. The implementation and analysis in this study are important for designing more accurate and efficient VQE methods, thus enhancing the potential utilization of quantum computers in quantum simulation algorithms.